Getting a Grip on Your Feelings Effects of Action Orientation and External Demands on Intuitive Affect Regulation. (article). - Koole, Sander L.
The authors propose that volitional action is supported by intuitive affect regulation, define as flexible, efficient , and nonrepressive control of own affective states. Intuitive affect regulation should be most apparent among action-oriented individuals under demanding conditions. Consistent with this, a demanding context led action-oriented individuals to down-regulate negative affect in self-reports. (Study 1), in an affective Simon task (Study 2), and in an face discrimination task (Study 3). In line with the idea that intuitive affect regulation is guided by top-down self-regulation processes, intuitive affect regulation in a face discrimination task was mediated by increases in self-accessibility (Study 3). No parallel effects emerged among action-oriented participants in a nondemanding context or among state-oriented participants. -- (from the author).
Keywords: Psychology-Periodicals.